Pendidikan Islam Buya Hamka - Kartika, Dwi; Muhammad Guntur Alting (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In order to address the problem of value and moral imbalance that plagues the modern education system, this study aims to define the theory of Islamic education as understood by Buya Hamka. Hamka's books are collected as the main source for this study, and an assessment of him and his works is drawn from an analysis of other books. A qualitative research approach was used in this study. There is no other topic that can be explored and researched other than Hamka's views on education, particularly Islamic education in Indonesia. Maximum efforts in strengthening and developing individuals are emphasized in Buya Hamka's thought system on Islamic education. The findings of this study organize the manner in which Hamka's ideas developed, showing the relationship between his personal experiences and the common thread of his educational philosophy. To determine the applicability of Hamka's philosophy of Islamic education to current conditions, the author then conducts an analytical analysis of Hamka's thoughts in relation to these conditions. If this is done, it has the potential to improve people's lives in this country